2019
DOI: 10.3390/w11051107
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Groundwater Contamination Risk with Radon Based on Clustering and Structural Models

Abstract: There is currently some controversy in the scientific community regarding the efficiency of the water–rock interaction process in the contamination of radon in groundwater. In this study, some difficulties were found in the sampling phase. Many of the water collection points are used for human consumption. As such, some municipalities did not want to collaborate. When this natural contaminant is undetectable to the human sense and may cause pulmonary neoplasms in the long term, it is difficult to obtain collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…For instance, when there is not mobilization of radon from rocks to water, it becomes crucial to understand which factors may be preventing this transfer process. Previous studies in fractured aquifer systems have reported that there is not a direct relationship between high-radon contents in rocks and the significant contamination of groundwater [2], [6], [7]. Then, how is it justified when in this comparison there is a high-radon production in rocks and a reduced radon concentration in groundwater?…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…For instance, when there is not mobilization of radon from rocks to water, it becomes crucial to understand which factors may be preventing this transfer process. Previous studies in fractured aquifer systems have reported that there is not a direct relationship between high-radon contents in rocks and the significant contamination of groundwater [2], [6], [7]. Then, how is it justified when in this comparison there is a high-radon production in rocks and a reduced radon concentration in groundwater?…”
Section: Introductionmentioning
confidence: 94%
“…Radon contamination in drinking water is invisible to human sense, and as such, should be given particular attention when a high radioactive exposure in drinking water occurs. For a practical assessment of aquifer contamination risk, it is useful to establish a conceptual model that explains the production and transport of radon from rocks to drinking water [2]- [5]. For instance, when there is not mobilization of radon from rocks to water, it becomes crucial to understand which factors may be preventing this transfer process.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations